Dos jardins à proteção da biodiversidade planetária: as ações de proteção das sementes crioulas em uma experiência na Índia, França e Brasil - Silva, Clayton Rodrigues França (2013)
This work aimed to investigate the experiences of environmental change from the protective actions of native seeds, that serve as a strategic model to guarantee food sovereignty and biodiversity protection. In which, for the development of research, some actions were observed from three organizations and movements: Navdanya, Kokopelli and Sementes da Paixão, operating in countries with different cultural and socioeconomic - India, France and Brazil, respectively. However, they have the same intent with respect to policy and sustainable actions for the protection and cultivation of varieties of food crops. These practices are conducte in a safe way that respects the environment and their own cultural diversities while the development of creating genetically modified seeds alter the natural cycles of development and regeneration of nature, breaking bonds required for its maintenance, as well as autonomy, freedom of choice to feed and produce of farmers and consumers. The cultivation and protection of native seeds is a way of narrowing and return to a harmonious relationship, a period in which the man was part of nature. It is an act of liberation and a right to life.